ANALISIS FAKTOR YANG MENJADI PENENTU MAHASISWA DALAM MEMILIH PERGURUAN TINGGI - Endang Ruhiyat (Universitas Pamulang, 2016)
ANALYSIS OF FACTORS DETERMINANT STUDENTS IN CHOOSING UNIVERSITY. Background on why this research is due to intense competition in the